Horizontal Integration An Administrative Science Perspective on Cross-Border Cooperation in Europe - Beck, Joachim (Nomos Verlagsgesellschaft mbH & Co. KG, 2022)
The European border regions perform a specific horizontal integration function. From the perspective of public administration theory, this publication lays the foundations for conceptualising the policy area of cross-border cooperation in Europe as a horizontal level of integration. To this end, the volume analyses the integration theory specifics of its genesis, the functional particularities of its governance with regard to the decentralised integration of different political-administrative, legal and cultural systems, as well as the patterns of emergent, transnational territorial institutionalism. Finally, administrative perspectives on the study of cross-border cooperation as a horizontal level of the European Administrative Area are also presented.